Liver Disease Secondary to Milligan - Morgan: a Report of 2 Cases - Wang, Xinyu; Zhao, Xin; Zhang, Xi (Journal of Contemporary Medical Practice, 2024)
Milligan - Morgan (M-M) is the traditional surgery way of treating hemorrhoids at home and abroad, but the larger surgery surgical trauma and postoperative wound healing time is longer, wound care undeserved easy to trigger a surgical site infection, bacteria into the blood may also cause other parts of the infection. This paper reports 1 cases of mixed hemorrhoid external strip in postoperative secondary process of diagnosis and treatment of patients with bacterial liver abscess, 1 cases of mixed hemorrhoid external strip in postoperative patients with secondary Liver injury after the diagnosis and treatment. This study provides a reference for the prevention, diagnosis and treatment of such complications in patients with mixed hemorrhoids.